Chemical Tagging of Protein Lipoylation. Issue 8 (21st December 2020) - Tang, Qi; Guo, Yilan; Meng, Liying; Chen, Xing
Abstract: Protein lipoylation is a post‐translational modification of emerging importance in both prokaryotes and eukaryotes. However, labeling and large‐scale profiling of protein lipoylation remain challenging. Here, we report the development of iLCL (iodoacetamide‐assisted lipoate‐cyclooctyne ligation), a chemoselective reaction that enables chemical tagging of protein lipoylation. We demonstrate that the cyclic disulfide of lipoamide but not linear disulfides can selectively react with iodoacetamide to produce sulfenic acid, which can be conjugated with cyclooctyne probes. iLCL enables tagging of lipoylated proteins for gel‐based detection and cellular imaging. Furthermore, we apply iLCL for proteomic profiling of lipoylated proteins in both bacteria and mammalian cells. In addition to all of the eight known lipoylated proteins, we identified seven candidates for novel lipoylated proteins. The iLCL strategy should facilitate uncovering the biological function of protein lipoylation. Abstract : The iLCL (iodoacetamide‐assisted lipoate‐cyclooctyne ligation) strategy enables chemoselective tagging, cellular imaging, and proteomic profiling of a rare but central post‐translational modification, namely protein lipoylation in both bacteria and mammalian cells.